Cost-effectiveness of mirogabalin for the treatment of post-herpetic neuralgia in Taiwan. (3rd May 2020) - Ye, Xin; Gray, Emma; Wang, Yen-Feng; Wang, Shuu-Jiun
Abstract: Objectives: To assess the cost-effectiveness of mirogabalin versus no treatment or pregabalin in patients with post-herpetic neuralgia (PHN) from a third-party perspective in Taiwan. Methods: A Markov model, which was developed with 2-week cycles and 1-year time horizon from the Taiwanese National Health Insurance Administration perspective, consisted of three health states: "mild, " "moderate, " and "severe" pain. Average daily pain score (ADPS) was assessed at the end of each cycle. Patients either remained in, or transitioned from, their assigned health state to a different state according to their pain score changes. All patients entered the model in "moderate" (4 ≤ ADPS <7) or "severe" (7 ≤ ADPS ≤ 10) pain health states. Efficacy data was informed by the pivotal Phase III trial, or by a network meta-analysis (NMA). Utility values were obtained from published literature and cost data from Taiwanese clinical experts and the Taiwan National Health Insurance Administration, using 2018 New Taiwan dollar (NT). Probabilistic analysis was conducted to test the robustness of base case results. Results: Head-to-head analysis showed mirogabalin 30 mg to be cost-effective versus placebo in PHN. The deterministic analysis estimated a quality-adjusted life years gain of 0.041 at an ICER of NT11, 231 (US365) versus no treatment (ICER: NT274, 567 [US8, 900]). In the NMAs, mirogabalin was cost-effective compared to pregabalin 150 mg (ICER: NT515, 881 [US16, 720]) and 300 mg (ICER: NT201, 671 [US6, 535]). Mirogabalin 30 mg dominated pregabalin 600 mg. Results from sensitivity and scenario analyses confirmed these results. Conclusion: Mirogabalin 30 mg, a potent and selective α2δ ligand, is a cost-effective treatment option for PHN in Taiwan, with ICERs below the willingness-to-pay threshold.